SOCIO-PSYCHOLOGICAL FACTORS OF BEHAVIOR FORMATION IN ADOLESCENTS. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Adolescence is a condition of special manifestation of psychological characteristics, in which certain changes occur as a result of extraordinary influences. This article talks about the socio-psychological factors of behavior formation in adolescence